CONSULTING AS A PEDAGOGICAL GUIDANCE TECHNOLOGY IN THE CONTINUOUS EDUCATION OF A PEDAGOGUE - Lukashenia, Zoya; Sianiuta, Natallia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present day tendency of rapid constant changes of the informational and technological space surrounding a pedagogue, suggests the necessity of continuous education. The necessity of constant renovation of knowledge leads a pedagogue to obtain new competences, to the emergence of new educational practices. As a result of high competition in all spheres of society the client-orientated course of modern system of professional education makes a pedagogue search for new forms of getting competences, which are not set in the frames of certain disciplines and thus provide the continuity of educational processes. Here we suggest consulting, having been worked out as a pedagogical technology that guaranties the achievement of the set goals, reproduction and replication. The purpose of our research is to substantiate the expediency of using the pedagogical technology of consulting to support the process of continuous professional training of a teacher directly at the workplace. The article deals with the theoretical stage results of our research in working out a consulting model as a pedagogical technology of continuous pedagogue’s educational guidance as well as the analysis of pedagogue-participants’ opinions concerning the pilot approbation of this model.